Love saves the day [large type] : a novel - Cooper, Gwen, 1971- (Thorndike Press, 2013)
When five-week-old Prudence meets a woman named Sarah in a deserted construction site on Manhattan's Lower East Side, she knows she's found the human she was meant to adopt. For three years their lives are filled with laughter, tuna, catnaps, music, and the unchanging routines Prudence craves. Then one day Sarah doesn't come home, and Laura, the daughter who hardly ever visits, arrives with her husband. And they're carrying boxes.